Effect of special exercises on blood biochemical indices in highly skilled athletes of cyclic sports events with endurance manifestation during pre-start preparation - Vynohradov, V.; Osypenko, G.; Ilyin, V.; Vynogradova, O. A.; Rusanova, O. (Journal of Physical Education and Sport, 2020)
The paper presents complexes of physical exercises and mobilization sports massage for skilled female athletes specialized in rowing. The positive influence of such complexes on pre-start preparation, which is quite relevant, is shown. Objective of study: Evaluating the influence of different complexes of pre-start special exercises and mobilization massage in two versions of their combinations on biochemical indices of blood serum in highly skilled female athletes specialized in rowing during pre-start preparation. Subjects and methods of study: The study involved 4 female athletes - international-class masters of sports in rowing. Questionnaire was conducted before the first test to assess the subjective state of female athletes on a 10-point scale, a biochemical blood test (Mindray BS200 Chemistry Analyzer). Athletes performed different exercise complexes during pre-start warm up. Blood serum cortisol and testosterone levels, their ratio (T/C index), as well as the activity of cellular enzymes: ALT, AST, LDH, GGT, ALP were determined before and after application of impacts. Testosterone and cortisol content were determined by means of BECKMAN COULTER Access 2 and immunoenzymatic method (MR-96A Mindray), respectively. Results. The influence of complexes of impacts on female athlete hormonal status alteration has been shown. After performing complex 1, the decrease of blood cortisol content was observed in all subjects after 5 and 40 minutes of rest. After 40 minutes of rest blood cortisol level decreased by 40%, 34% and 24 % in the first, the second and the third, and the fourth female athlete. Total average decrease of testosterone level constituted 27 %. After completing complex 2 blood cortisol level decreased by 24 % and 21 % in the first and the second female athlete. Testosterone content decreased by 2 % and 7 %. T/C index constituted 0,0037 before and 0,0047 after in the first female athlete and 0,0030 before and 0,0036 after in the second one. A 25 % increase in the T/C ratio after performing this complex was noted in the second athlete. To analyze the results of the study, methods of statistical data processing and those of nonparametric statistics were used. Conclusions. The peculiarities of biochemical reactions in the body of highly skilled female athletes to the impacts of special exercises. Different degree and direction of changes in blood serum cortisol and testosterone content, the T/C index of athletes, depending on the type of applied complexes, have been identified.